Computer Modelling and Detectability Assessment of the Transition Zone in the Basement Complex Terrain of Southwest Nigeria - Ademilua, Oladimeji Lawrence (2015)
The main objective of this research was to theoretically model a basement profile containing the transition zone with varying thicknesses and resistivities as a means of assessing the detectability of this zone. This was because the zone has the tendency to be suppressed on the Vertical Electrical Sounding (VES) curve due to its intermediate resistivity and often thin thickness.